Health Inequalities Critical Perspectives - Smith, Katherine; Bambra, Clare; Hill, Sarah (Oxford University Press, 2015)
The UK has been recognized as a global leader in health inequalities research and policy. Yet, despite post-1997 policy commitments, by most measures the UK's health inequalities have continued to widen. This failure has prompted calls for new approaches to health inequalities research and policy, alongside a growing sense that public health researchers ought to be more actively involved in 'public health advocacy'. However, there is currently no agreement as to what these new research agendas should be or precisely what it is that public health egalitarians ought to be advocating. This book aims to address these gaps. It begins by taking stock of the UK's experiences of health inequalities research and policy to date, reflecting on the lessons that have been learnt from these experiences, both within the UK and internationally. It then moves on to identify emergent research and policy topics, exploring the perspectives of actors working in a range of professional settings on these agendas. Finally, the book considers potential ways of improving the links between health inequalities research, policy, and practice, including via advocacy.